Assessing Elementary Teachers’ Competence in Designing HOTS-Based ANBK Items: A Case Study in Cluster I, Sungaipua District - Ricky Gustiawan; Ardipal Ardipal; Yalvema Miaz; Zelhendri Zen (AL-ISHLAH: Jurnal Pendidikan, 2025)
Teachers are expected to possess a range of professional competencies, one of which is the ability to design effective learning evaluations. This study investigates the ability of grade V teachers to develop Higher Order Thinking Skills (HOTS) questions aligned with the National Assessment (ANBK), the steps they follow in question development, and the challenges they encounter in the process. A qualitative case study approach was employed, involving one group of four elementary schools in the Sungaipua Cluster 1. Data were collected through observation, interviews, and documentation. The analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. Findings reveal that most grade V teachers lack the necessary skills to construct ANBK-based HOTS questions. This is attributed to varying educational backgrounds and a limited understanding of the ANBK framework. Additionally, teachers often bypass the process of developing original question items, relying instead on questions sourced from the internet. Their limited knowledge of proper question design procedures further hampers their ability to develop effective assessments. A key challenge identified is that the lack of teacher proficiency in HOTS question design translates into student difficulties in mastering higher-order thinking competencies. These findings suggest a need for targeted professional development to enhance teachers’ understanding and skills in HOTS-aligned assessment practices.